Global Diversification and Distribution of Coronaviruses With Furin Cleavage Sites - Liu, Xiaotong; Wu, Qunfu; Zhang, Zhigang (Frontiers in Microbiology, 2021)
The hydrolysis of glycoproteins on the cell membrane mediated by furin cleavage site is essential for both MERS-CoV and SARS-CoV-2 to infect humans. However, the knowledge of Coronaviruses (CoVs) with furin cleavage sites is still extremely limited. Here, we illustrated global epidemiology and evolutionary history of SARS-CoV-2 and other 248 CoVs with 86 diversified furin cleavage sites have appeared in 24 animal hosts in 28 countries over at least 60 years. Besides MERS-CoV and SARS-CoV-2, two of other five known CoVs to infect humans also carry furin cleavage sites, including HCoV-OC43 and HCoV-HKU1. Notably, the human enteric coronavirus 4408 with a furin cleavage site was first detected in Germany in 1988 but considered to be unable to infect human. Conclusively, the presence of furin cleavage sites might explain polytropic nature of the SARS-CoV-2 or SARS-CoV-2-like CoVs, which would be helpful to prevent the COVID-19 pandemic and even outbreak of novel CoVs.